2013
DOI: 10.3390/ijms14035312
|View full text |Cite
|
Sign up to set email alerts
|

Cold Signaling and Cold Response in Plants

Abstract: Plants are constantly exposed to a variety of environmental stresses. Freezing or extremely low temperature constitutes a key factor influencing plant growth, development and crop productivity. Plants have evolved a mechanism to enhance tolerance to freezing during exposure to periods of low, but non-freezing temperatures. This phenomenon is called cold acclimation. During cold acclimation, plants develop several mechanisms to minimize potential damages caused by low temperature. Cold response is highly comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
311
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 415 publications
(319 citation statements)
references
References 199 publications
5
311
0
3
Order By: Relevance
“…Nuclear Ca 2+ is increased after cold treatment and the maximum increase is delayed at 5-10 s compared to the peak of cytosolic calcium (Miura & Furumoto 2013). Mauger (2012) reported that the increase in nuclear Ca 2+ is caused by a nuclear envelope that is considered one of the major Ca 2+ stores.…”
Section: Gene Expression Induction In Response To Low Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear Ca 2+ is increased after cold treatment and the maximum increase is delayed at 5-10 s compared to the peak of cytosolic calcium (Miura & Furumoto 2013). Mauger (2012) reported that the increase in nuclear Ca 2+ is caused by a nuclear envelope that is considered one of the major Ca 2+ stores.…”
Section: Gene Expression Induction In Response To Low Temperaturementioning
confidence: 99%
“…Many coldregulated miRNAs have been recognized using bioinformatics, cloning and sequencing tools in different plant species (Zhou et al 2008;Zhang et al 2009;Lv et al 2010;Chen et al 2012). However, only a little is known about the mi target genes that are unregulated under the effect of low temperature (Miura & Furumoto 2013).…”
Section: Gene Expression Induction In Response To Low Temperaturementioning
confidence: 99%
“…In Arabidopsis, the SIZ1-mediated sumoylation (at K393) of the MYC-type transcription factor ICE1 is required to activate cold signaling and freezing tolerance (Miura et al 2007b), and the introduction of an ICE1(K393R) variant protein represses the expression of cold-responsive genes and reduces freezing tolerance. ICE1-dependent cold signaling for cold acclimation is highly conserved among plants (Miura and Furumoto 2013). For example, the overexpression of tomato ICE1 enhances chilling tolerance and the accumulation of antioxidants, several amino acids, and sugars in red tomato fruits (Miura et al 2012a;Miura et al 2012b).…”
mentioning
confidence: 99%
“…Notably, cold acclimation in plants is a potent inducer of salicylic acid and ethylene accumulation [47][48][49][50], transcription factors [40], calcium signaling [51,52], pathogenesis-related and antifungal proteins [5] along with anatomical changes, and cell membrane or cytoskeleton restructuring [53]. Consequently, besides plant antioxidative systems several other host factors should be considered as potential mechanisms behind the observed resistance response in cold hardened barley challenged by infection with P. teres f. teres.…”
Section: Discussionmentioning
confidence: 99%